The Moderating Role of QRIS on the Effect of Price and Promotion toward UNNES Students’ Purchasing Decisions for MSME Products - Fatimah, Siti; Moh. Eko Saputro (Universitas Negeri Semarang, 2025)
This research is motivated by the innovation implemented by most MSMEs in the UNNES area in the non-cash payment system in the form of QRIS. This study aims to analyze the effect of the QRIS system in moderating prices and promotions on UNNES students' purchasing decisions. The method used in this study is moderation regression analysis (MRA), which is analyzed using SPSS, and data collection using questionnaire techniques. The research sample is students who used MSME goods and services around the campus. The findings of this study indicate that price and promotion remain key factors influencing students' purchasing decisions. In contrast, using QRIS does not moderate the relationship between these variables and purchasing behavior. This outcome suggests that students prioritize price and promotional offers over payment. Furthermore, students perceive that using QRIS may encourage increased spending, which is problematic given their typically limited financial resources. As a result, QRIS is often regarded as a secondary payment option, used only after cash, due to concerns about its potential to reduce spending control.